Criminal Penalties for Wildlife Trafficking: A Green Victimology Perspective - Rakisa Wijaya Kusuma, Daffa Prangsi; Pulungan, Muhammad Mukhtar (Contemporary Issues in Criminal Law, 2024)
This study focuses on the analysis of the application of the green victimology concept in criminal penalties for the trafficking of protected wildlife in Indonesia. This is a crucial issue since protected wildlife has not received proper attention as victim of crimes and is still seen as an object of trafficking. The study analyses ten court decisions in the last 10 years that have decided on protected wildlife trafficking cases. The purpose of this study is to identify how the green victimology concept views the criminal imposition of protected wildlife trafficking. The method used is normative legal research with a case study and conceptual approach. The results of this study show that green victimology is important to consider as a perspective that can aid in criminal sentencing. This is derived from the notion that recognizing animals as victim of crime will provide a more comprehensive perspective in looking at the entire justice system. This study also seeks to formulate a number of parameters for the application of green victimology concept in criminal sentencing that combines CITES, IUCN Red list, and deterrent sentencing objectives as key parameters for criminal sentencing. Based on these parameters, the authors did not find a certain pattern in the criminal imposition of wildlife trafficking cases. This can have implications from the absence of a clear philosophical basis, the potential for criminal disparities to conflict with the values of justice that are developing in society. This study recommends that guidelines for criminal penalties in wildlife trafficking cases be prepared by using the green victimology concept as the primary perspective basis. This is so that the verdict can accommodate the recognition of animals as victims and is oriented towards prevention efforts for crimes of similar nature. Keywords: Green Victimology, Trafficking in Protected Wildlife, Criminal Punishment. Abstrak Penelitian ini berfokus pada analisis terhadap penerapan green victimology dalam penjatuhan pidana atas perkara perdagangan satwa liar yang dilindungi di Indonesia. Isu tersebut penting dikarenakan satwa liar yang dilindugi belum mendapatkan perhatian yang layak sebagai korban kejahatan dan masih dipandang sekedar sebagai objek perdagangan. Penelitian ini akan menganalisis sepuluh putusan pengadilan dalam rentang 10 tahun terakhir yang memutus perkara perdagangan satwa liar yang dilindungi. Tujuan penelitian ini adalah untuk mengetahui bagaimana green victimology memandang penjatuhan pidana atas perdagangan satwa liar yang dilindungi. Metode yang digunakan adalah penelitian hukum normatif dengan pendekatan kasus dan konseptual. Hasil penelitian ini menunjukkan bahwa green victimology penting untuk dipertimbangkan sebagai perspektif yang dapat membantu dalam penjatuhan pidana. Hal tersebut dikarenakan dengan merekognisi hewan sebagai korban kejahatan akan memberikan perspektif yang lebih komprehensif dalam memandang keadilan. Penelitian ini juga berusaha untuk merumuskan sejumlah parameter aplikasi green victimology dalam penjatuhan pidana yang mengkombinasikan CITES, IUCN Redlist, tujuan pemidanaan detterent sebagai parameter kunci penjatuhan pidana. Berdasarkan parameter tersebut, kami tidak menemukan adanya pola tertentu dalam penjatuhan pidana perkara tindak pidana perdagangan satwa liar. Hal tersebut dapat berimplikasi dari ketiadaan dasar filosofis yang jelas, potensi disparitas pemidanaan hingga bertentangan dengan nilai keadilan yang berkembang dalam masyarakat. Penelitian ini merekomendasikan untuk disusun pedoman penjatuhan pidana dalam kasus perdagangan satwa liar dengan menggunakan green victimology sebagai basis perspektif utama. Hal tersebut agar putusan yang dijatuhkan dapat mengakomodir rekognisi hewan sebagai korban dan berorientasi pada upaya pencegahan kejahatan dengan karakteristik serupa. Kata kunci: Green Victimology, Perdagangan Satwa Liar yang Dilindungi, Penjatuhan Pidana.